Régimen jurídico de los bienes de interés cultural de los monasterios y conventos que dejan de estar abandonados - González-Varas Ibañez, Alejandro (Revista española de derecho canónico, 2017)
Legal regime of the cultural goods of the monastries and convents that are left This article analyzes the legal situation of the goods belonging to monastries and convents that are to be closed. It is an increasing phenomenon in countries that have had an old Christian tradition - such as Spain-, and nowadays they are undergoing a situation of progressive secularization. Both real estate and movable property usually have an important historical-artistic importance, which affects their use and legal treatment. This article begings studying the legal mechanisms provided by Canon Öaw in order to suppress a house. Afterwards, it will be possible to know who will be the new owner of the goods. It will also be necessary to address the legal-canonical and civil regime that affects ist conservation and, where appropriate, the transfer of objects